Developing E-Writing Materials for The Junior High School Students - Khoiriyah Fathur (IJET (Indonesian Journal of English Teaching), 2019)
This study aims at developing appropriate e-writing material to meet the needs of the students of MTs Negeri Kota Pasuruan. The teaching materials were developed to facilitate students’ psychological aspect and achieve their pedagogical goal. These materials which are based on the English Curriculum standard of content were developed in the form of interactive CD-ROM. It provides scaffolding flowing from fully guided, partly guided, to fully free learning. The study employs a design and development model of Richey and Klein (2007) with three main stages: identifying research problem phase realized through needs analysis, model development research, and model validation research for both internal and external validation. The result of the data from the students shows that the final product can be regarded as an appropriate e-writing material for the students. The data are supported by the result obtained from English teachers; these materials reflect constructivism, questioning, inquiry, learning community, modeling, reflection, and authentic assessment. Therefore, these materials which reflect Contextual Teaching and learning (CTL) are categorized as a very good material and no revision needed.